Turnaround Success in High Technology Growth Stage Firms - TenBrink, Candace; Keller, Robert T.; Gelb, Betsy (Journal of Management Policy and Practice, 2017)
Firms in growth industries face frequent innovation cycles, environmental ambiguity, and time-based pressures that often lead to performance declines or failure. This study explores actions and firm circumstances that are associated with successful growth stage turnarounds. We apply life cycle theory to a sample of technology-based firms with the aim of clarifying what factors enable a timely turnaround in the context of a growth industry. We find that successful turnarounds are significantly associated with a smaller firm size and with a more severe decline. These results offer implications for life cycle theory and add depth to turnaround literature